Analisis Penerapan Model Pembelajaran LoK-R terhadap Kemampuan Literasi Siswa Kelas V dalam Pembelajaran Bahasa Indonesia - Puspitasari, Lindayanti; Satriyawan, Aziz Nuri; Nafsi, Ifaafah Izatun; Setiawan, Rudik (IBTIDA', 2024)
The aim of this research is to analyze the application of learning models LoK-R (Learning-Oriented Reading in the Language Classroom) and its impact on the literacy skills of class V students in understanding Indonesian language material at MI Nurul Iman. The research methodology uses a descriptive qualitative approach with data collection techniques through classroom observations, interviews with Indonesian language educators, and analysis of the implementation of Lok-R learning and understanding of material regarding students’ literacy skills in learning Indonesia. The findings show that the learning modelLoK-R considered relevant and effective in improving students' literacy skills. Educators highlight the advantages of this model in encouraging students' active participation, increasing their understanding, and strengthening interest in learning. However, constraints such as limited time and resources, as well as challenges in adapting the model to students' needs were also identified. To overcome these obstacles, strategies such as efficient time management, maximum management of available resources, adapting the model to students' needs, developing educator capacity, and collaboration and institutional support have been identified. The research results show that this approach is considered relevant and effective in improving students' literacy skills. Educators also admit that this model encourages active student participation, deepens understanding of the material, and increases interest in learning. This research provides valuable insight for educators and schools to improve the quality of understanding of Indonesian language material and students' literacy skills. With a deep understanding of the impacts and obstacles in implementing the learning model LoK-R, appropriate steps can be taken to increase the effectiveness of understanding the material.